TEKNIK KALIBRASI HEIGHT GAUGE MENGACU PADA JIS B 7517-2018 - Stephen Alexander Sembiring; Aulia Fajrin; Annisa Fyona; Mutiarani; Hendra Butar Butar; Ita Wijayanti (Politeknik Negeri Batam, 2026)
This study evaluates the performance of a Mitutoyo dial height gauge (resolution 0.01 mm, range 0–600 mm) in accordance with JIS B 7517-2018 through deviation analysis and repeatability assessment at nine set points (20–600 mm), using a certified Grade 0 gauge block as reference standard under laboratory conditions of 20 ± 1 °C and 50–60% relative humidity. The maximum deviation recorded was −0.0033 mm (at the 20 mm set point), below the Maximum Permissible Error (MPE) of ±0.020 mm per JIS B 7517-2018. The largest repeatability value was 0.01 mm, satisfying the standard limit. All nine measurement points passed the conformance criteria. A consistent negative deviation pattern at set points ≤ 200 mm indicates a minor systematic error correlated with Abbe principal violation at short measurement ranges, with direct implications for quality assurance in precision manufacturing.